The Influence of Factors Product, Price, Place and Promotion on Purchasing Decisions of Students at Coffeeshop - Amany, Ahmad Asad; Wahyudi, Tri Nur (Proceedings International Conference on Education Innovation and Social Science, 2025)
This research aims to explore how factors like product, price, promotion, and place influence the buying decisions of students at coffee shops near Universitas Muhammadiyah Surakarta. Using a quantitative approach, the study features an associative and cross-sectional design. The participants were students who frequented these coffee shops, with a sample size of 100 respondents gathered through volunteer sampling. Data collection was carried out by distributing online surveys via Google Forms, employing a Likert scale for measurement. The research tool was assessed for both validity and reliability, showing that all items had a validity score above 0.30, and Cronbach's Alpha reliability was an impressive 0.928, indicating very high consistency. For data analysis, multiple linear regression was used to evaluate both the combined and individual effects of the independent variables (product, price, promotion, place) on the dependent variable (purchase decision). The results revealed that all four independent variables significantly impact student purchasing decisions (p < 0.05; R² = 0.741). Specifically, the promotion (X4) and place (X3) variables had a notable effect (p < 0.05), while price (X2) and product (X1) did not show significant effects (p > 0.05). This indicates that factors like location convenience and effective promotions play a more crucial role in shaping students' buying choices than product and price. Therefore, it’s recommended that coffee shop owners focus on improving location accessibility and marketing strategies to attract and retain customers, especially students.